Synthesis of Modified C-Nucleosides of Therapeutic Significant: A Succinct Account - Hudait, Nandagopal; Sakander, Norein; Kundu, Sanchari; Rasool, Bisma; Sengupta, Jhimli; Mukherjee, Debaraj (Synlett, 2023)
Since their discovery in the 1950s, C-nucleosides have piqued the interest of both biologists and medicinal chemists. In this regard, C-nucleosides and their synthetic analogues have resulted in promising leads in drug design. Concurrently, advances in chemical syntheses have contributed to structural diversity and drug discovery efforts. Convergent and modular approaches to synthesis have gained much attention in this regard. Among them nucleophilic substitution at C-1 has seen wide applications, providing flexibility in synthesis, good yields, the ability to maneuver stereochemistry as well as to incorporate structural modifications. In this account, we briefly discuss the modular synthesis of C-nucleosides with a focus on mechanistic studies and sugar modifications that have resulted in potent lead molecules. Meanwhile, various FDA-approved C-nucleoside analogues have been reported previously for their antiviral and/or anticancer potential, with examples being pyrazomycin, remdesivir, pseudouridine, and pseudouridimycin.1 Introduction and Motivation2 Strategies for the Synthesis of C-Nucleosides3 Biologically Active C-Nucleosides4 Mechanistic Analysis of C-Nucleoside Formation5 Synthesis and Manipulation of Medicinally Important C-Nucleoside Analogues6 C-Nucleosides: Synthesis of C–C Bonds with a C-1′ Base7 Conclusion
Keywords: nucleosides; nucleobases; glycosylation; DNA; drugs; medicinal chemistry